Associations between body composition and lifestyle factors with bone mineral density according to time since menopause in women from Southern Brazil: a cross-sectional study. Issue 1 (December 2015) - Silva, Thaís; Franz, Roberta; Maturana, Maria; Spritzer, Poli
Abstract Background The aim of this study was to investigate whether body composition, dietary pattern and habitual physical activity are associated with BMD according to time since menopause in women from Southern Brazil with no clinical evidence of disease. Methods 99 participants were enrolled and anthropometry, body composition and BMD by dual energy x-ray absorptiometry, rest metabolic rate by indirect calorimetry, dietary pattern by semi quantitative food frequency questionnaire and habitual physical activity by pedometer were performed. Results Mean age was 55.2 ± 4.9 years and mean time since menopause was 6.8 ± 1.0 years. Weight, BMI, lean and fat mass and RMR were higher in women with less than 5 years since menopause with normalversus low bone mass. No differences were found in the studied variables between participants with normal or low bone mass and more than 5 years of menopause. Women with > 5 years since menopause had higher prevalence of osteoporosis, as well as lower BMD in all sites when compared to those with less time since menopause. Calories, carbohydrate, protein, fat and micronutrients intake were similar between groups. When the sample was adjusted for time since menopause, the odds ratio (OR) for low bone mass was 5.21 (95 % CI 1.57–17.25, P = 0.004) for BMI <25 kg/m2, for lean mass <37.5 Kg an OR of 4.4 (95 % CI 1.64–11.80, P = 0.004, for fat mass <26.0 Kg an OR of 3.39 (95 % CI 1.29–8.85, P = 0.010) and for the intake of vitamin A < 700 mcg/day an OR of 3.00 (95 % CI 1.13–7.94, P = 0.012). Low meat and eggs intake or low protein intake did not influence the odds ratio for low bone mass. Conclusion In this cross-sectional study with postmenopausal women with no clinical evidence of disease, time since menopause, low lean and fat mass were associated with low bone mass. Calories and macronutrients intake as well as habitual physical activity did not interfere with BMD, but participants were mostly sedentary. Further studies are needed in order to determine whether the adequate intake of specific food groups and the type of physical activity could attenuate the time since menopause impact on BMD.